Op weg na "n post-kritiese Nuwe-Testamentiese Wetenskap - Vorster, W. S. (Hervormde teologiese studies, 1987)
Heading for a post-critical New Testament Science This essay is an investigation into the shifts which are taking place in New Testament scholarship in terms of scientific paradigms and epistemologies. It explores the relations between domain assumptions and the ontological, epistemological, social, teleological and methodological dimensions of critical and post-critical paradigms in use. It is an attempt to explain the underlying currents in contemporary developments in New Testament scholarship.